Bibliometrics of Scholarly Communications Published in the Journal of Information Science Theory and Practice from 2013 to 2022 - Garg, Kailash Chandra (Journal of Data Science, Informetrics, and Citation Studies)
The study aims to present a bibliometric analysis of the scholarly communications published in the journal from 2013 to 2022. The study makes a quantitative and qualitative analysis of papers published in the journal using the publication and the citation data for these papers. Publication data for the study was downloaded from the Website of the journal and the citation data was obtained from Google Scholar. The different bibliometric indicators used in the study for analysis are Citation Per Paper (CPP), i-10 index and Papers not Cited (PnC). The analysis considers different entities like publishing countries, institutions and authors for examining the publication output and their citation impact. Based on the analysis, it is observed that the journal followed a consistent trend of publishing papers during the period of study from 2013 to 2021, with an exception in the number of publications in the year 2022. Among the countries, Korea topped the list and among the institutions KISTI and its different affiliates ranked first, though Korea as well as KISTI had a low citation influence. CPP is highest for Heinrich Heine University (Germany). Eighteen different countries published 66 papers in domestic collaboration and among these Korea topped the list with 20 papers. Korea also topped the list of countries for papers published in international collaboration. The study may be useful for obtaining a quick snapshot of countries, institutions, and authors that are publishing papers in the journal besides reflecting the citation impact of the papers for these entities.
Keywords: Bibliometrics; Scientometrics; Journal of Information Science Theory and Practice; JISTaP; KISTI.